POLITICAL ARTICULATION OF GUS MUS’ ASCETICISM IN STRENGTHENING THE ROLE OF NU AS A MORAL FORCE IN NATIONAL POLITICS - Khoiron, Khoiron; Anadza, Hirshi; M, Abdul Wahid (JWP (Jurnal Wacana Politik), 2024)
This study reveals the practice of articulation of ascetic politics carried out by Gus Mus amidst the strong democratic regime that dictated the process of contestation of power at the NU Congress in 2015 in Jombang. The practice of articulation of asceticism is political, because he always changes his identity. As a subject, Gus Mus often changes positions, such as a kiai and a cultural figure. This position is called the subject position. This study explores the creation of a new identity in contemporary politics using Laclau’s articulation theory within a post-structuralist case study research design. Therefore, the main argument in this study is that through the political articulation of asceticism, Gus Mus’ political reasoning transcends the Laswellian mainstream political reasoning. This study uses a qualitative method, with two methods in data collection, namely interview and documentation methods. The informants were selected using purposive sampling techniques, and data analysis used discourse analysis which was completely within the theoretical frame used by the researcher. This study does not only shift from a positivist paradigm to a post-positivism research, but from a focus on thoughts to a focus on the discourse articulated by Gus Mus from the perspective of actors from both the NU 2015 Congress committee and the NU elite in Jombang, and from here, the novelty in this study. In this study, the political practice of asceticism articulated by Gus Mus was found in: a). Discourse in the articulation of intellectualism, b). Modesty, c). Beyond practical politics, and d). Consistency in cultural politics. From here, “new political ethics” is relevant and vital as an alternative political thought for recent political actors.